The severely atrophic maxilla: Decision making with zygomatic and pterygoid dental implants - Alexandre Amir Aalam; Alina Krivitsky-Aalam; Gregori M. Kurtzman; Lanka Mahesh (Elsevier, 2023)
The severely atrophic maxilla can present with some challenges during treatment planning with communication between those performing the surgical and prosthetic aspects of the treatment as well as communication with the patient as to what is being suggested for treatment. This article simplifies the communication and understanding of treating the severely atrophic maxilla and based on the Bedrossian classification gives a guideline for the surgical approach to be adapted based on the patient residual anatomy.